Literatur Review : Penerapan Strategi Pemasaran Digital dan Kolaborasi Influencer dalam Meningkatkan Kesadaran Merek - Jajang Roni Aunul Kholik; Irawan R.D. Budianto (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
In the face of an increasingly changing and rapidly developing environment, companies and brands must adapt quickly to remain relevant and well known in the eyes of consumers. Two key elements that are emerging and increasingly popular in order to increase brand awareness are effective digital marketing and company collaboration with influencers. In order to understand and increase brand awareness, it is important to identify the factors that influence brand awareness. This research was conducted to determine and analyze the application of digital marketing strategies and collaboration with influencers in increasing brand awareness. This research method was carried out using a descriptive analysis approach using qualitative methods and literature study by examining theories in books and online journals. The research results show that digital marketing strategies to increase brand awareness can be carried out through the use of social media, search engine optimization (SEO), paid advertising, email marketing and relevant online content. Meanwhile, influencer collaboration in increasing brand awareness can be done through steps, namely understanding the Influencer's target audience and influence on their followers, selecting relevant Influencers, as well as creative and authentic content.